2018
DOI: 10.1051/matecconf/201817001118
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable economic development at the meso level: factors and ratings

Abstract: Abstract. Existing approaches to assessing the sustainability of an economic system that is in a state of reform or in a transition period (industry, region) have some disadvantages. Some approaches can be applied only to static systems or systems with a stable structure, while others do not have predictive properties. Therefore, there is a need to develop a methodology that can provide a more accurate conclusion about the sustainability and prospects of an industry or region undergoing organizational reform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This contributes to the consolidation of knowledge, obtaining innovative solutions and the introduction of economically and environmentally efficient technologies in the field of waste management. The implementation of the concept of sustainable development of the region is possible if environmental problems are addressed through the implementation of innovative achievements [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contributes to the consolidation of knowledge, obtaining innovative solutions and the introduction of economically and environmentally efficient technologies in the field of waste management. The implementation of the concept of sustainable development of the region is possible if environmental problems are addressed through the implementation of innovative achievements [11].…”
Section: Resultsmentioning
confidence: 99%
“…This determines the relevance of the selected topic. What is the infrastructure of the waste processing cluster, what is its essence and what tasks does its formation solve is the goal of this study [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the positive impact of the development of the virtual labor market, the researchers emphasize the possibility of solving a number of urgent problems. These include the adaptation of white collars released in the process of digitalization; prevention of stagnant unemployment; involvement of socially vulnerable strata of the population in the economically active population, solution of environmental problems [1,[14][15][16][17]. Taking into account the possibilities of the virtual labor market, it was concluded that it can help to find ways to adapt to such serious challenges from the external environment as changing the nature of many professions or their complete disappearance [18][19][20], shortening the life cycle of a profession and strengthening the role of competencies, the polarization of the employed and the gradual displacement of professions requiring an average level of qualifications [21], an increase in the period of retirement [22].…”
Section: Methodsmentioning
confidence: 99%
“…Thirdly, the lack of digital skills and internal barriers related to the company's culture and thinking are the biggest obstacles to digital progress in the energy sector. About 71% of organizations in the industry need staff with joint experience working with domains and digital technologies, and 18% claim that they do not have a single employee with such a combined set of skills [22].…”
Section: Methodsmentioning
confidence: 99%